PENDIDIKAN ISLAM DALAM PERSPEKTIF PROF. DR. HJ. ZAKIAH DARADJAT - Hamida Olfah (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This paper analyzes Islamic education in the perspective of Zakiah Daradjat. is one of the figures of Indonesian Islamic education who pays great attention to Islamic education. This can be seen in his works and his direct involvement in the world of education. His ideas contributed greatly to the world of Indonesian Islamic education in particular. The method used in this study is library research, what is meant by literature research is research activities carried out by collecting data in the form of books, papers, articles, magazines, journals, web (internet) and the results of previous research that which is related to the ideas and thoughts of Zakiyah Daradjat in the field of Islamic education. The question to be answered in this paper is, how is Islamic education in the perspective of Zakiah Daradjat. The result of this study is, Islamic education in the perspective of Zakiah Daradjat is seen when he formulates and maps about the nature and objectives of Islamic education, the basis of Islamic education and the environment and responsibility of Islamic education.